A high-strength engineering plastic, preparation and nondestructive testing method thereof
By using the combination of PA and PET composite materials and carbon fiber in engineering plastics, a comprehensive performance evaluation model is established, which solves the cost and accuracy challenges of existing non-destructive testing methods, and achieves efficient and accurate detection results.
Patent Information
- Application Number
- CN202411006525.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-25
AI Technical Summary
Existing non-destructive testing methods have challenges in testing cost and accuracy, especially affected by the material, shape, surface status and skill level of the inspected object, which may lead to errors.
Polyamide (PA) and polyethylene terephthalate (PET) are used as matrix resin, carbon fiber is added as conductive filler, and compatibility agents, liquid crystal polymers and other additives are added to prepare high-strength engineering plastics. By establishing a comprehensive performance evaluation model, the stability of material performance is judged and non-destructive testing is carried out based on the model results, reducing the detection difficulty and cost.
New engineering plastics with high strength, high toughness, good heat resistance and chemical corrosion resistance are achieved, reducing the cost and difficulty of non-destructive testing and improving the accuracy and efficiency of testing.
Smart Images

Figure CN118909430B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of data processing and relates to a high-strength engineering plastic, a preparation method and a nondestructive testing method thereof. Background Art
[0002] With the rapid development of modern industry, the requirements for material performance are increasing day by day. As an important polymer material, engineering plastics have been widely used in aerospace, automobile manufacturing, electronic appliances, medical equipment and other fields due to their excellent mechanical properties, chemical stability, processing performance and other characteristics.
[0003] In the production of engineering plastics, non-destructive testing technology plays a vital role. Non-destructive testing can detect internal or surface defects without destroying the object being tested, avoiding material waste and cost increase caused by testing. In addition, non-destructive testing usually has a faster detection speed and higher detection efficiency. At the same time, different detection methods and parameters can be selected according to actual needs, with high flexibility. Through non-destructive testing, relevant personnel can monitor the performance changes of materials in the preparation process in real time, and promptly discover and correct possible ratio problems. At the same time, non-destructive testing can also be used to verify whether the performance of the final product meets the expected requirements, ensuring that the material can achieve optimal performance in actual applications. However, some non-destructive testing methods require the use of expensive testing equipment and consumables, resulting in relatively high testing costs. In addition, the accuracy of non-destructive testing results is affected by many factors such as the material, shape, surface state of the object being tested and the skill level of the tester, and there may be certain errors.
[0004] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0005] The first object of the present invention is to provide a method for preparing high-strength engineering plastics, using a composite of polyamide (PA) and polyethylene terephthalate (PET) as a matrix resin, using carbon fiber as a conductive filler, and adding other additives to prepare the high-strength engineering plastics, optimizing the performance data of the above materials, and establishing a comprehensive performance evaluation model including the content of each component to determine whether the performance test results in the production of the high-strength engineering plastics are stable.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions:
[0007] A high-strength engineering plastic, which is prepared by compounding PA and PET to obtain a matrix resin, using carbon fiber as a conductive filler, and adding a compatibilizer, liquid crystal polymer and other additives;
[0008] The tensile strength, flexural strength and electrical conductivity of the high-strength engineering plastic are taken as key performance indicators, and a comprehensive performance evaluation model is established between the key performance indicators. Based on the comprehensive performance evaluation model, it is judged whether the performance test results in the production of the high-strength engineering plastic are stable, and the parts that deviate from the theoretical comprehensive performance are marked according to the performance stability judgment results, and then non-destructive testing is performed on the marked parts.
[0009] PA has good toughness and impact resistance, while PET has excellent heat resistance, chemical corrosion resistance and good optical properties. The combination of the two can give full play to their respective advantages, achieve complementary performance, and significantly improve the comprehensive performance of the composite material. Through the combination of PA and PET, new engineering plastics with high strength, high toughness, good heat resistance and chemical corrosion resistance can be developed, thereby broadening its application areas in extreme environments, such as high temperature and high pressure environments, highly corrosive media, etc.
[0010] Furthermore, a compatibilizer is required between the two resins PA and PET to assist molecular penetration and entanglement. Good compatibility helps to form a uniform composite material structure, reduce defects caused by poor interface bonding, and thus improve the reliability of nondestructive testing. Too little addition of carbon fiber may not form an effective conductive network, and too much addition may affect the processing performance and cost of the composite material. The present invention is based on the above-mentioned materials, determines the optimal dosage of each component through data processing, and determines the theoretical value and difference threshold of the comprehensive performance index on the basis of the determination of the optimal dosage, and sequentially detects the performance of the materials in production, thereby exempting the data with the measured performance within the difference threshold range from inspection, and performing nondestructive testing on the data outside the difference threshold range, thereby reducing the difficulty of material detection.
[0011] A method for preparing high-strength engineering plastics comprises the following steps:
[0012] S1: Determine the empirical quantities of base resin, conductive filler, compatibilizer, liquid crystal polymer and other additives;
[0013] S2: Use orthogonal experimental design to systematically arrange different components and their content levels to form an experimental matrix;
[0014] S3: Prepare samples with different formulations according to the experimental matrix design and use a twin-screw extruder for extrusion granulation;
[0015] S4: Set tensile strength, flexural strength and electrical conductivity as key performance indicators of high-strength engineering plastics; perform key performance tests on each sample, collect test data and record the performance results of each formula;
[0016] S5: Define key performance indicators as dependent variables and the content of each component as independent variables, use variance analysis and regression analysis to analyze the impact of each factor on the performance indicators, and determine the most important factors and their optimal levels;
[0017] S6: Calculate the correlation between tensile strength, flexural strength and electrical conductivity, and establish a comprehensive performance evaluation model;
[0018] S7: setting a difference threshold based on the difference between the comprehensive performance evaluation model and the theoretical value obtained from the comprehensive performance index model based on the comprehensive performance evaluation model combined with the nondestructive testing evaluation.
[0019] Furthermore, in S1, the empirical mass ratios of the matrix resin, conductive filler, compatibilizer, liquid crystal polymer and other additives are: PA: 40-50%; PET: 30-40%; carbon fiber: 10-20%; compatibilizer: 1-5%; liquid crystal polymer: 0.5-2%; other additives: 0.1-5%. The above scheme is the empirical proportions preliminarily determined by the inventor after theoretical research, in which the compatibilizer uses ethylene-acrylic acid copolymer (EAA), maleic anhydride grafted polypropylene (PP-g-MAH) and other components, and PA and PET can be evenly distributed by lowering the melting point or improving the compatibility. Liquid crystal polymer (LCP) is a high-performance engineering plastic with a liquid crystal structure. Its high strength and high modulus can significantly improve the tensile strength and flexural strength of the composite material. Enhance the rigidity and wear resistance of the composite material.
[0020] Furthermore, in S2, an orthogonal experimental design was used to systematically arrange different components and their content levels to form an experimental matrix;
[0021] In the present invention, the melting point of PA is about 190-250°C. The melting point of PET is about 250-260°C. Based on the melting points of PA and PET, the preparation methods of each formulation in the orthogonal experiment are prepared using the same steps, which specifically include the following steps:
[0022] First, the carbon fiber is surface treated, cleaned and dried for later use;
[0023] Then, PA and other hygroscopic materials are dried for later use;
[0024] Add the base resin, compatibilizer, liquid crystal polymer and other additives into the high-speed mixer in proportion for preliminary mixing; ensure that the components are evenly distributed;
[0025] Then, on the basis of uniform premixing, the pretreated carbon fiber is added to continue mixing; at the same time, the ultrasonic dispersion equipment is turned on to perform ultrasonic-assisted dispersion on the carbon fiber;
[0026] The mixed raw materials are transferred to a twin-screw extruder for melt blending and extrusion molding. According to the characteristics of the raw materials, the aspect ratio of the twin-screw extruder is 36:1, and the temperature of each section of the barrel is set as follows: 50°C in zone 1, 190°C in zone 2, 250°C in zone 3, 260°C in zone 4, 255°C in zone 5, 250°C in zone 6, 250°C in zone 7, 250°C in zone 8, 255°C in zone 9, and the die temperature is 255°C. The main engine speed is 300r / min.
[0027] Further, in S4, key performance tests are performed on each sample, test data are collected and performance results of each formulation are recorded as follows;
[0028] Furthermore, in S5, variance analysis is used to determine the significance of each factor on the performance index; including:
[0029] Ensure that all experimental data are recorded, including the levels of each component and the corresponding key performance indicators;
[0030] The key performance indicators were used as dependent variables, and the content of each component was used as an independent variable, and an ANOVA table was constructed using statistical software;
[0031] Calculate the variance contribution of each independent variable to the dependent variable;
[0032] The significance of the content of each component was determined by the F test;
[0033] Taking the key performance indicators as dependent variables and all significant independent variables in variance analysis as independent variables, using statistical software to input data for regression analysis;
[0034] TS=a 11 X 1 +a 12 X 2 +a 13 X 3 +a 14 X 4 +a 15 X 5 +...+a 1n X n +B 1 ;
[0035] FS=a 21 X 1 +a 22 X 2 +a 23 X 3 +a 24 X 4 +a 25 X 5 +...+a 2n X n +B2 ;
[0036] EC=a 31 X 1 +a 32 X 2 +a 33 X 3 +a 34 X 4 +a 35 X 5 +...+a 3n X n +B 3 ;
[0037] Among them, TS is the tensile strength value, FS is the bending strength value, EC is the electrical conductivity value; X 1 is the content of PA; X 2 is the content of PET; X 3 is the content of conductive filler; X 4 is the content of compatibilizer; X 5 is the content of liquid crystal polymer; X n is the content of other additives; a 11 to a 3n is the regression coefficient, B 1 To B 3 It should be noted that, due to data processing in the present invention, each data does not contain a unit, that is, it is expressed as an output value.
[0038] Further, in S6, the correlation between tensile strength, bending strength and electrical conductivity is calculated, and a comprehensive performance evaluation model is established; including:
[0039] The Pearson correlation coefficient was used to calculate the correlation between tensile strength, flexural strength and electrical conductivity;
[0040] According to the results of correlation analysis, different weights are assigned to tensile strength, flexural strength and electrical conductivity;
[0041] A comprehensive performance index model for tensile strength, flexural strength and electrical conductivity was established using a comprehensive weighted scoring method.
[0042] Independent recipe combination data are selected as the validation set to verify the comprehensive performance index model.
[0043] Furthermore, in S6, the comprehensive performance indicator model is:
[0044] Y=m 1 TS+m 2 FS+m 3 EC;
[0045] Among them, Y is the comprehensive performance index, m1 、m 2 、m 3 is the weight coefficient; TS is the tensile strength value, FS is the bending strength value, and EC is the electrical conductivity value.
[0046] Further, in S7, based on the difference between the comprehensive performance evaluation model and the measured comprehensive performance index in combination with the nondestructive testing evaluation and the theoretical value obtained in the comprehensive performance index model, setting the difference threshold means:
[0047] Use a twin-screw extruder to extrude and granulate the determined formula; perform key performance tests on samples and collect test data; use the same testing personnel, test techniques and test equipment to perform non-destructive testing on samples, evaluate the difference between the measured comprehensive performance indicators of non-damaged products and the theoretical values obtained in the comprehensive performance indicator model, and set the difference threshold.
[0048] The second object of the present invention is to provide a non-destructive testing method for high-strength engineering plastics, so as to realize non-full inspection of engineering plastics, that is, to exempt the parts whose difference from theoretical comprehensive performance index is within the difference threshold range from inspection, thereby reducing the difficulty and cost of inspection.
[0049] The above technical objectives of the present invention are achieved through the following technical solutions:
[0050] According to the nondestructive testing method for high-strength engineering plastics prepared by the above method, the comprehensive performance indicators of high-strength engineering plastics are monitored in real time and compared with the theoretical values obtained in the comprehensive performance indicator model, and it is judged whether the difference is within the difference threshold range. If not, ultrasonic scanning technology, resistance imaging technology or electromagnetic nondestructive testing technology is used to identify and locate the part where the measured comprehensive performance deviates from the theoretical performance indicator.
[0051] In the preparation of high-strength engineering plastics, the dispersion of carbon fiber and the formation of a conductive network are particularly important. As a conductive filler, the uniform dispersion of carbon fiber and the formation of an effective conductive network in the matrix resin are crucial to product performance. The integrity of the conductive network directly affects the propagation and reflection of electromagnetic waves in the composite material, and then affects the accuracy and sensitivity of non-destructive testing. In addition, the dispersion of carbon fiber also affects the processing performance of the composite material. If the carbon fiber is unevenly dispersed, defects such as bubbles and delamination will occur in the composite material during processing, and the corresponding comprehensive performance will also change. The present invention monitors the comprehensive performance indicators of high-strength engineering plastics in real time and compares them with the theoretical values obtained in the comprehensive performance indicator model, and identifies the abnormal data part, thereby reducing the detection cost.
[0052] In summary, the present invention has the following beneficial effects:
[0053] The present invention systematically arranges different components and their content levels through orthogonal experimental design, and can more comprehensively explore the influence of each component on the performance of high-strength engineering plastics, thereby quickly determining the optimal formula and significantly improving the preparation efficiency and quality. On this basis, variance analysis and regression analysis are used to accurately analyze the influence of various factors on key performance indicators such as tensile strength, flexural strength and conductivity, determine the most important factors and their optimal levels, and then achieve optimization of material performance.
[0054] The present invention calculates the correlation between tensile strength, flexural strength and conductivity, establishes a comprehensive performance evaluation model, can comprehensively evaluate the overall performance of the material, and provide a more scientific basis for the selection and application of the material. After selecting the optimal formula, a verification test is carried out to ensure that the prepared high-strength engineering plastic has stable and consistent performance and meets the actual application requirements. In actual production, after setting the optimal ratio, the comprehensive performance that can be achieved is determined. By real-time monitoring of the performance data of engineering plastics, the part that deviates greatly from the theoretical comprehensive performance is specifically identified, reducing the difficulty of monitoring.
[0055] The high-strength engineering plastics prepared by the present invention can be nondestructively tested in real time using resistance imaging technology or electromagnetic nondestructive testing technology in actual production, and can accurately identify and locate defects inside the material, further improving the quality and reliability of the material. Not only does it optimize the preparation process of high-strength engineering plastics, improve preparation efficiency and quality, but it also realizes comprehensive evaluation and nondestructive testing of material properties, providing strong support for the wide application of high-strength engineering plastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 A schematic flow chart of a method for preparing high-strength engineering plastics is provided for the embodiment of the present application; DETAILED DESCRIPTION
[0057] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a high-strength engineering plastic, preparation and non-destructive testing method thereof, its specific implementation method, characteristics and effects are described in detail as follows.
[0058] The present invention provides a method for preparing high-strength engineering plastics. The high-strength engineering plastics are prepared by compounding PA and PET to obtain a matrix resin, using carbon fiber as a conductive filler, and adding a compatibilizer, a liquid crystal polymer and other additives; the other additives include one or more of a heat stabilizer, an antioxidant, a lubricant, and a coupling agent;
[0059] The tensile strength, flexural strength and electrical conductivity of the high-strength engineering plastic are taken as key performance indicators, and a comprehensive performance evaluation model is established between the key performance indicators. Based on the comprehensive performance evaluation model, it is judged whether the performance test results in the production of the high-strength engineering plastic are stable, and the parts that deviate from the theoretical comprehensive performance are marked according to the performance stability judgment results, and then non-destructive testing is performed on the marked parts.
[0060] A method for preparing high-strength engineering plastics comprises the following steps:
[0061] S1: Determine the empirical quantities of base resin, conductive filler, compatibilizer, liquid crystal polymer and other additives;
[0062] S2: Use orthogonal experimental design to systematically arrange different components and their content levels to form an experimental matrix;
[0063] S3: Prepare samples with different formulations according to the experimental matrix design and use a twin-screw extruder for extrusion granulation;
[0064] S4: Set tensile strength, flexural strength and electrical conductivity as key performance indicators of high-strength engineering plastics; perform key performance tests on each sample, collect test data and record the performance results of each formula;
[0065] S5: Define key performance indicators as dependent variables and the content of each component as independent variables, use variance analysis and regression analysis to analyze the impact of each factor on the performance indicators, and determine the most important factors and their optimal levels;
[0066] S6: Calculate the correlation between tensile strength, flexural strength and electrical conductivity, and establish a comprehensive performance evaluation model;
[0067] S7: Based on the comprehensive performance evaluation model combined with lossless;
[0068] Furthermore, in S1, the empirical mass ratios of the matrix resin, conductive filler, compatibilizer, liquid crystal polymer and other additives are: PA: 40-50%; PET: 30-40%; carbon fiber: 10-20%; compatibilizer: 1-5%; liquid crystal polymer: 0.5-2%; other additives: 0.1-5%. The above scheme is the empirical proportions preliminarily determined by the inventor after theoretical research, in which the compatibilizer uses ethylene-acrylic acid copolymer (EAA), maleic anhydride grafted polypropylene (PP-g-MAH) and other components, and PA and PET can be evenly distributed by lowering the melting point or improving the compatibility. Liquid crystal polymer (LCP) is a high-performance engineering plastic with a liquid crystal structure. Its high strength and high modulus can significantly improve the tensile strength and flexural strength of the composite material. Enhance the rigidity and wear resistance of the composite material.
[0069] Furthermore, in S2, taking the other additives as thermal stabilizers as an example, an orthogonal experimental design was used to systematically arrange different components and their content levels to form an experimental matrix;
[0070]
[0071]
[0072] In the present invention, the melting point of PA is about 190-250°C. The melting point of PET is about 250-260°C. Based on the melting points of PA and PET, the preparation methods of each formulation in the orthogonal experiment are prepared using the same steps, which specifically include the following steps:
[0073] First, the carbon fiber is surface treated, cleaned and dried for later use;
[0074] Then, PA and other hygroscopic materials are dried for later use;
[0075] Add the base resin, compatibilizer, liquid crystal polymer and other additives into the high-speed mixer in proportion for preliminary mixing; ensure that the components are evenly distributed;
[0076] Then, on the basis of uniform premixing, the pretreated carbon fiber is added to continue mixing; at the same time, the ultrasonic dispersion equipment is turned on to perform ultrasonic-assisted dispersion on the carbon fiber;
[0077] The mixed raw materials are transferred to a twin-screw extruder for melt blending and extrusion molding. According to the characteristics of the raw materials, the aspect ratio of the twin-screw extruder is 36:1, and the temperature of each section of the barrel is set as follows: 50°C in zone 1, 190°C in zone 2, 250°C in zone 3, 260°C in zone 4, 255°C in zone 5, 250°C in zone 6, 250°C in zone 7, 250°C in zone 8, 255°C in zone 9, and the die temperature is 255°C. The main engine speed is 300r / min.
[0078] Further, in S4, key performance tests are performed on each sample, test data are collected and performance results of each formulation are recorded as follows;
[0079] Experiment No. Tensile strength(MPa) Bending strength(MPa) Conductivity (S / cm) 1 75 110 4.5 2 80 115 4.8 3 85 120 5 4 82 118 4.7 5 87 122 5.2 6 79 112 4.6 7 90 125 5.3 8 83 117 4.9 9 79 114 4.7
[0080] Furthermore, in S5, variance analysis is used to determine the significance of each factor on the performance index; including:
[0081] Ensure that all experimental data are recorded, including the levels of each component and the corresponding key performance indicators;
[0082] The key performance indicators were used as dependent variables, and the content of each component was used as an independent variable, and an ANOVA table was constructed using statistical software;
[0083] Calculate the variance contribution of each independent variable to the dependent variable;
[0084] The significance of the content of each component was determined by the F test; the significance level of each independent variable on the dependent variable was shown to be p < 0.05.
[0085] Furthermore, in S5, the key performance indicators were used as dependent variables, and all significant independent variables in the variance analysis were used as independent variables, and the data were input into the statistical software for regression analysis;
[0086] TS=a 11 X 1 +a 12 X 2 +a 13 X 3 +a 14 X 4 +a 15 X 5 +...+a 1n X n +B 1 ;
[0087] FS=a 21 X 1 +a 22 X 2 +a 23 X 3 +a 24 X 4 +a 25 X 5 +...+a 2n X n +B 2 ;
[0088] EC=a 31 X 1 +a 32 X 2 +a 33 X 3 +a 34 X 4 +a 35 X 5 +...+a 3n X n +B 3 ;
[0089] Among them, TS is the tensile strength value, FS is the bending strength value, EC is the electrical conductivity value; X 1 is the content of PA; X 2 is the content of PET; X 3 is the content of conductive filler; X 4 is the content of compatibilizer; X 5is the content of liquid crystal polymer; X n is the content of other additives; a 11 to a 3n is the regression coefficient, B 1 To B 3 is a constant term. The above data are all numerical values and do not include units.
[0090] The present invention systematically arranges different components and their content levels through orthogonal experimental design, and can more comprehensively explore the influence of each component on the performance of high-strength engineering plastics, thereby quickly determining the optimal formula and significantly improving the preparation efficiency and quality. On this basis, variance analysis and regression analysis are used to accurately analyze the influence of various factors on key performance indicators such as tensile strength, flexural strength and conductivity, determine the most important factors and their optimal levels, and then achieve optimization of material performance.
[0091] Further, in S6, the correlation between tensile strength, bending strength and electrical conductivity is calculated, and a comprehensive performance evaluation model is established; including:
[0092] The Pearson correlation coefficient was used to calculate the correlation between tensile strength, bending strength and conductivity. Specifically, the Pearson correlation coefficient between tensile strength and bending strength was 0.87, the correlation coefficient between tensile strength and conductivity was 0.65, and the correlation coefficient between bending strength and conductivity was 0.70. This shows that there is a strong positive correlation between tensile strength and bending strength, and a moderate positive correlation between tensile strength and conductivity, and between bending strength and conductivity.
[0093] According to the results of correlation analysis, different weights are assigned to tensile strength, flexural strength and electrical conductivity;
[0094] A comprehensive performance index model for tensile strength, flexural strength and electrical conductivity was established using a comprehensive weighted scoring method.
[0095] Independent recipe combination data are selected as the validation set to verify the comprehensive performance index model.
[0096] The present invention calculates the correlation between tensile strength, flexural strength and conductivity, establishes a comprehensive performance evaluation model, can comprehensively evaluate the overall performance of the material, and provide a more scientific basis for the selection and application of the material. After selecting the optimal formula, a verification test is carried out to ensure that the prepared high-strength engineering plastic has stable and consistent performance and meets the actual application requirements. In actual production, after setting the optimal ratio, the comprehensive performance that can be achieved is determined. By real-time monitoring of the performance data of engineering plastics, the part that deviates greatly from the theoretical comprehensive performance is specifically identified, reducing the difficulty of monitoring.
[0097] Furthermore, in S7, the weight of the tensile strength is set to 0.4, the weight of the bending strength is set to 0.35, and the weight of the conductivity is set to 0.25.
[0098] Furthermore, in S7, the comprehensive performance indicator model is:
[0099] Y = 0.4TS + 0.35FS + 0.25EC;
[0100] Among them, Y is a comprehensive performance index, TS is tensile strength, FS is bending strength, and EC is electrical conductivity.
[0101] Furthermore, in S7, a twin-screw extruder is used to extrude and granulate the determined formula; key performance tests are performed on the samples and test data is collected; non-destructive testing is performed on the samples using the same testing personnel, the same testing techniques and testing equipment, and the difference between the measured comprehensive performance indicators of the non-damaged products and the theoretical values obtained in the comprehensive performance indicator model is evaluated, and a difference threshold is set.
[0102] On this basis, the present invention also provides a non-destructive testing method for high-strength engineering plastics. During production, the comprehensive performance indicators of high-strength engineering plastics are monitored and compared with the theoretical values obtained in the comprehensive performance indicator model, and it is determined whether the difference is within the difference threshold range. If not, ultrasonic scanning technology, resistance imaging technology or electromagnetic non-destructive testing technology is used to identify the part of the measured comprehensive performance that deviates from the theoretical performance indicator.
[0103] The high-strength engineering plastics prepared by the present invention can be nondestructively tested in real time using resistance imaging technology or electromagnetic nondestructive testing technology in actual production, and can accurately identify and locate defects inside the material, further improving the quality and reliability of the material. Not only does it optimize the preparation process of high-strength engineering plastics, improve preparation efficiency and quality, but it also realizes comprehensive evaluation and nondestructive testing of material properties, providing strong support for the wide application of high-strength engineering plastics.
[0104] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention in any form. Although the present invention has been presented as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A nondestructive testing method for high-strength engineering plastics, characterized in that: The high-strength engineering plastic is prepared by compounding PA and PET to obtain a matrix resin, using carbon fiber as a conductive filler, and adding a compatibilizer, liquid crystal polymer and other additives; The tensile strength, flexural strength and electrical conductivity of the high-strength engineering plastic are used as key performance indicators, a comprehensive performance evaluation model is established between the key performance indicators, whether the performance test results in the production of the high-strength engineering plastic are stable is judged based on the comprehensive performance evaluation model, and the part that deviates from the theoretical comprehensive performance is marked according to the performance stability judgment result, and then non-destructive testing is performed on the marked part; The method for preparing the high-strength engineering plastic comprises: S1: Determine the empirical quantities of base resin, conductive filler, compatibilizer, liquid crystal polymer and other additives; S2: Use orthogonal experimental design to systematically arrange different components and their content levels to form an experimental matrix; S3: Prepare samples with different formulations according to the experimental matrix design and use a twin-screw extruder for extrusion granulation; S4: Set tensile strength, flexural strength and electrical conductivity as key performance indicators of high-strength engineering plastics; perform key performance tests on each sample, collect test data and record the performance results of each formula; S5: Define key performance indicators as dependent variables and the content of each component as independent variables, use variance analysis and regression analysis to analyze the impact of each factor on the performance indicators, and determine the most important factors and their optimal levels; S6: Calculate the correlation between tensile strength, flexural strength and electrical conductivity, and establish a comprehensive performance evaluation model; S7: setting a difference threshold based on the difference between the comprehensive performance evaluation model and the theoretical value obtained from the comprehensive performance index model in combination with the nondestructive testing assessment of the measured comprehensive performance index; In S5, variance analysis was used to determine the significance of each factor on the performance index; including: Ensure that all experimental data are recorded, including the levels of each component and the corresponding key performance indicators; The key performance indicators were used as dependent variables, and the content of each component was used as an independent variable, and an ANOVA table was constructed using statistical software; Calculate the variance contribution of each independent variable to the dependent variable; The significance of the content of each component was determined by the F test; Taking the key performance indicators as dependent variables and all significant independent variables in variance analysis as independent variables, using statistical software to input data for regression analysis; Wherein, TS is the tensile strength value, FS is the bending strength value, EC is the conductivity value; X1 is the content of PA; X2 is the content of PET; X3 is the content of conductive filler; X4 is the content of compatibilizer; X5 is the content of liquid crystal polymer; X n is the content of other additives; a 11 to a 3n are regression coefficients, B1 to B3 are constant terms; In S6, the correlation between tensile strength, flexural strength and electrical conductivity is calculated, and a comprehensive performance evaluation model is established; including: The Pearson correlation coefficient was used to calculate the correlation between tensile strength, flexural strength and electrical conductivity; According to the results of correlation analysis, different weights are assigned to tensile strength, flexural strength and electrical conductivity; A comprehensive performance index model for tensile strength, flexural strength and electrical conductivity was established using a multi-objective optimization method; Selecting independent recipe combination data as a validation set to validate the comprehensive performance index model; In S6, the comprehensive performance indicator model is: Among them, Y is the comprehensive performance index, m1, m2, and m3 are weight coefficients; TS is the tensile strength value, FS is the bending strength value, and EC is the electrical conductivity value.
2. The nondestructive testing method for high-strength engineering plastics according to claim 1, characterized in that: The other additives include one or more of a heat stabilizer, an antioxidant, a lubricant, and a coupling agent.
3. The nondestructive testing method for high-strength engineering plastics according to claim 1, characterized in that: In S1, the empirical mass proportions of matrix resin, conductive filler, compatibilizer, liquid crystal polymer and other additives are: PA: 40~50%; PET: 30~40%; carbon fiber: 10~20%; compatibilizer: 1~5%; liquid crystal polymer: 0.5~2%; other additives: 0.1~5%.
4. The nondestructive testing method for high-strength engineering plastics according to claim 1, characterized in that: In S3, The matrix resin, compatibilizer, liquid crystal polymer and other additives are added to a high-speed mixer in proportion for preliminary mixing; then the pretreated carbon fiber is added for further mixing; at the same time, the ultrasonic dispersion equipment is turned on to perform ultrasonic-assisted dispersion of the carbon fiber; then the evenly mixed raw materials are transferred to a twin-screw extruder for melt blending and extrusion molding.
5. A nondestructive testing method for high-strength engineering plastics according to any one of claims 1 to 4, characterized in that: In S7, based on the difference between the comprehensive performance evaluation model and the measured comprehensive performance index in combination with the nondestructive testing evaluation and the theoretical value obtained in the comprehensive performance index model, setting the difference threshold means: Use a twin-screw extruder to extrude and granulate the determined formula; perform key performance tests on samples and collect test data; use the same testing personnel, test techniques and test equipment to perform non-destructive testing on samples, evaluate the difference between the measured comprehensive performance indicators of non-damaged products and the theoretical values obtained in the comprehensive performance indicator model, and set the difference threshold.
6. A nondestructive testing method for high-strength engineering plastics according to claim 5, wherein nondestructive testing is performed on samples whose difference between the measured comprehensive performance index and the comprehensive performance index model is outside the difference threshold, characterized in that: During production, the comprehensive performance indicators of high-strength engineering plastics are monitored and compared with the theoretical values obtained in the comprehensive performance indicator model, and it is determined whether the difference is within the difference threshold range. If not, ultrasonic scanning technology, resistance imaging technology or electromagnetic non-destructive testing technology is used to identify the part where the measured comprehensive performance deviates from the theoretical performance indicators.
Citation Information
Patent Citations
Polyethylene terephthalate composite material and method of producing the same
CN101153111A